A NEW APPROACH IN TREATMENT ACUTE IVERMECTIN TOXICITY IN MALE BALB-C MICE - Al-Rekabi, F. M. K .; Alsadawi, A.; Al-ameedi, Ali. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to investigate the potential therapeutic of flumazenil and neostigmine in single and combination in Balb-C mice subjected to ivermectin acute oral toxicity. Ivermectin-poisoning dose was considered the half dose of LD50 that computed in current study as 20.9 mg/kg BW. A total of 24 male Blub-C mice were divided randomly into four equal treatment groups and administered ivermectin-poisoning dose (10 mg/kg BW) and treated as follows: control group (C), treated orally with distilled water; neostigmine-treated group (NT), treated i.p. with 60 µg/kg BW of neostigmine; flumazenil-treated group (FT), treated i.p. with 7 µg/kg BW of flumazenil; and combination-treated group (CT), treated i.p. with 30 µg/kg BW of neostigmine plus 3.5 µg/kg BW of flumazenil. Oral administration of ivermectin at poisoning dose caused grooming, lethargy, depression, recumbency, with no mortalities recorded. The toxic signs of animals in FT and NT groups were disappeared within 1.23 and 1.98 h, respectively, comparing to animals in CT and C groups, in which the recovery time was prolonged to 40.62 and 4.52 h, respectively. Overall, both flumazenil and neostigmine medicines have the potential to overcome ivermectin acute poisoning in Bulb-C mice, with flumazenil being more efficient. However, the combination of both medicines can cause an adverse prognosis.